PEMBIAYAAN MUSYARAKAH DARI SISI PENAWARAN PADA PERBANKAN SYARIAH DI INDONESIA - Nunung Ghoniyah; Nurul Wakhidah (DHARMA EKONOMI, 2012)
The objective of this study is to know about musyarakah financing in offer side in syariah bank in Indonesia by using equity rasio variable, liability and profit sharing. The analyze used SPSS program. T-test and hierarchical regression analysis were used to test the hypotheses.  The result indicated that equity rasio and profit sharing have positive and significant relationship with musyarakah financing. Liability variable had no positive relationshipand significant with musyarakah financing. Beside, there was no diferentiation significanly between musyarakah financing in  syariah bank and syariah business unit. Kata kunci : musyarakah financing, equity, liability and profit sharing.